Combination therapy with Tamsulosin plus Dutasteride Versus Tamsulosin in Benign Prostatic Hyperplasia: a Systematic review & Meta-analysis - Behnam Amani; Majid Davari; Bahman Amani; Arash Akbarzadeh; Rouhollah Shabestan (Tehran University of Medical Sciences, 2023)
Background: This study aims to compare combination therapy efficacy and safety with tamsulosin plus dutasteride versus tamsulosin in benign prostatic hyperplasia. Methods:  An online search was conducted in PubMed, Cochrane Library, Embase, Scopus, and Web of Science to identify the relevant published studies up to July 2021. The reference list of the critical review articles was searched as well. The Cochrane risk of bias was used to assess the quality of studies. Meta-analysis was performed using the RevMan software v.5.3. Results:   Six studies, including 6647 patients, were included.  A  significant improvement was observed in the combination therapy group compared to the tamsulosin group in terms of international prostate symptom score (mean difference [MD]=-2.59, %95 confidence interval [CI]: -4.20 to -0.99; P=0.002), prostate volume (MD=-10.13, %95 CI: -12.38 to -7.88;  P<0.05), maximum urine flow rate (MD=1.05, %95 CI: 0.82 to 1.29; P<0.05), transitional zone volume (MD=-3.18, %95 CI: -3.57 to -2.79; P<0.05), and prostate-specific antigen (MD=-0.54, %95   CI: -0.80 to -0.29, P<0.05). The result of the subgroup showed that tamsulosin 0.2 mg in combination therapy was not effective in terms of international prostate symptom score (MD=-2.97; 95% CI: -7.49 to 1.56; P=0.20). Adverse events were more in combination therapy regarding erectile dysfunction, retrograde ejaculation, decreased libido, ejaculation failure, any adverse events, and any drug-related adverse event (P<0.05). However, there was no significant difference between the two groups regarding dizziness and any serious adverse event (P>0.05). Conclusion:  This meta-analysis showed that combination therapy has greater efficacy in treating patients with benign prostatic hyperplasia; however, it is associated with higher adverse events